Latent structure of psychosis in the general population: results from the Singapore Mental Health Study. Issue 1 (January 2014) - Subramaniam, M.; Abdin, E.; Vaingankar, J. A.; Verma, S.; Chong, S. A.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Few studies have examined the latent construct of psychotic symptoms or distinguished between the latent construct and its manifest indicators. The current study aimed to investigate the latent structure of psychotic symptoms using factor mixture modeling (FMM) and to use the best-fitting model to examine its sociodemographic and clinical correlates. Method The Singapore Mental Health Study (SMHS) was based on an adult representative sample of the Singapore population. Psychotic symptoms were assessed by using the Psychosis Screen section of the Composite International Diagnostic Interview version 3.0 (CIDI 3.0). FMM analyses were applied to determine the latent construct of psychotic symptoms. Sociodemographic and clinical correlates of the latent structure of psychosis symptoms were examined using multiple linear and logistic regression analyses. Results The overall weighted lifetime prevalence of any psychotic experience was 3.8% in the SMHS after excluding subthreshold experiences. The FMM analysis clearly supported the dimensional model of the latent structure of psychotic symptoms. On deriving the total score for 'psychosis symptoms' in accordance with the one latent trait model, and correlating it with sociodemographic factors, we found that female gender, vocational education, current and past smokers were positively associated with the 'psychosis' total score. Conclusions There is a need for an increased understanding of, and research into, this intermediate state of 'psychosis symptoms' that do not meet diagnostic criteria for psychosis. It is also important to learn more about the group of individuals in the community who may have preserved functioning to elucidate the protective factors that prevent transition to psychosis.